ANALISIS TEBAL PERKERASAN LENTUR JALAN DENGAN METODE BINA MARGA - Khaerunnisa, Virda; defiana, yanti; sumarno, wahyu (Jurnal Ilmiah Teknik Sipil, 2024)
The Tasikmalaya-Karangnunggal road section is one of the roads in Tasikmalaya Regency which is included in the category of provincial road status, the road section is located in the Cibalong-Parungponteng sub-district with a road length of 21,750 Kilometers, a road width of 6.5 meters, and a road shoulder of 2.5 meters. In general, the Tasikmalaya-Karangnunggal road section is in good condition, but at several points damage was found, either with potholes or bumps.As one of the roads that connect vital places, for example in shopping centers, education centers and other activities.With a high intensity of traffic flow and a large traffic load, it must be balanced with good road pavementIn this study the Bina Marga Method Pd T-01-2002-B was used to find the thickness of the flexible pavement. The data needed in finding the thickness of the flexible pavement is in the form of primary data obtained from direct field observations and secondary data obtained from the Department of Highways, Tasikmalaya Regency. The result of a flexible pavement with a design life of 20 years, with traffic growth of 5%, based on the Bina Marga Method Pd T-01-2002-B obtained 3,153,688,757.75Iss/Lajur/UR, the surface layer thickness of AC-WC was 4 cm, AC-BC 6 cm, class A aggregate was 15 cm, and class B aggregate was 26 cm .